Substent Anchor Technique for Recanalisation of a Full Metal Jacket Femoropopliteal In-Stent Occlusion. (2018) - Testi, Gabriele; Ceccacci, Tanja; Cevolani, Mauro; Acquati, Silvia; Tarantino, Fabio; Turicchia, Giorgio Ubaldo
Abstract : Purpose: To report the endovascular treatment of a full metal jacket (FMJ) femoropopliteal chronic total occlusion (CTO) using a new ancillary retrograde technique. Case report: An 80 year old woman with type 2 diabetes presented to the Diabetic Foot Clinic with critical limb ischaemia with tissue loss in the right leg. Her comorbidities included coronary artery disease, morbid obesity, hypertension, dyslipidaemia, and active smoking habit. The patient had been treated at another hospital by femoropopliteal FMJ stenting six years before this presentation. The duplex ultrasound showed a full length in-stent re-occlusion. An antegrade recanalisation was attempted via contralateral femoral access, but was unsuccessful. An ultrasound guided retrograde puncture of the popliteal artery in the P2 segment was performed very close to the distal occluded stent. A 0.018 guidewire was pushed in the substent plane, functioning as an anchor to achieve a stable system. The FMJ was then retrogradely recanalised with a second guidewire. The procedure was completed by antegrade angioplasty with drug coated balloons. Conclusion: The substent anchor technique can help to achieve stability even if close to the occluded stents, and spares the distal landing zone for surgical revascularisation if the endovascular approach fails. This technique could be useful in retrograde treatment of long in-stent CTO. Highlights: Recanalisation of in-stent chronic total occlusion is a challenging procedure. It is very difficult to treat long in-stent occlusion by an antegrade approach. The retrograde route allows for easier access to the stent true lumen. The distal landing zone should be spared for further surgical revascularisation. The substent anchor technique offers system stability as well as being close to the CTO.